Characteristics of thermal transpiration effect and the hydrogen flow behaviors in the microchannel with semicircular obstacle. (12th November 2019) - Ye, Jianjun; Shao, Junda; Hao, Zongrui; Salem, Shehab; Zhang, Yuan; Wang, Yiwen; Li, Zhengyang
Abstract: The thermal transpiration effect has great potential applications for the hydrogen energy. In this paper, the thermal transpiration effect and the hydrogen flow behaviors are studied in the microchannel with the semicircular obstacles. Firstly, the slip boundary model is used in the simulation of the flow performance in the microchannel. The validity of the model at different Kn is verified by comparing with some previous work. Then, the hydrogen flow characteristics of the thermal transpiration effect with the semicircular obstacle are investigated. The result shows that as the size of the semicircular obstacle increases, the hydrogen flow path of the thermal transpiration effect becomes longer, and the temperature gradient decreases. As the characteristic length of the hydrogen flow decreases, there is an obviously negative influence on the thermal transpiration flow. A deeper analysis shows that the thermal driven flow and the pressure driven flow will produce y -component velocity, which leads to a backflow under the effect of semicircles, and the semicircular obstacles make the Knudsen layer spread to the channel center. Highlights: The hydrogen flow behaviors in microchannel with semicircular obstacle. Semicircular obstacles affect the pressure increase of the hydrogen Knudsen compressor. Semicircular obstacles affect the state of the hydrogen flow through the channel. Semicircular obstacles in the microchannel affect the Knudsen layer.